An overview of carbon markets and emissions trading: Lessons for Canada - Michael R. King (Bank of Canada, 2008)
The author provides an overview of carbon markets and explains how emissions trading can be important in encouraging the reduction of CO2 emissions in an efficient manner. He describes the key steps in establishing a cap-and-trade system, and reviews the European experiences with emissions trading. He highlights the lessons learned from the EU Emissions Trading System on how to design a market that operates efficiently and effectively. By learning from the experience of other countries, Canada can avoid the uncertainty and volatility witnessed in carbon markets abroad while benefiting from an efficient trading mechanism that contributes to the welfare of all Canadians.
Keywords: D4; N50; Q21; 330; International topics; Market structure and pricing; Umweltpolitik; Kohlenstoff; Kohlendioxid; Emissionshandel; Wirkungsanalyse; USA; EU-Staaten; Kanada